Electronic Training (Distance Training): Its Justifications, Requirements and its Obstacles: Applied Study on a Sample of Trainers and Trainees - Al-Eissa, Ghzayel; Al-Omran, Afnan (The Arab Journal of Administration, 2021)
This study aimed to identify the requirements and justifications and obstacles of electronic training from the point of view of trainers and the trainee in the Deanship of Skills Development at King Saud University, biased on the descriptive survey. It was applied in the first semester of the academic year 1437/1438AH. The survey was conducted on a sample of (20) trainer and (384). The researcher used the questionnaire as a tool to collecting information. The study has reached a number of conclusions and recommendations the most important of which: the approval of trainers and trainees on the most requirements for electronic training is proficiency in running computer and peripherals and a team that provides technical support when needed. The most important justification for electronic training is the need to keep up with the development of knowledge, technical progress and prepare individuals to deal with it, the need of trainees to get training information to address urgent problems they may face in their way, as well as the development of techniques and the need to integrate them in training processes. It was also found that the obstacles that may face the electronic training were the administrative obstacles ranked from the point of view of trainers, and financial constraints from the point of view of trainees. The results of the study indicated that there were no statistically significant differences between the average responses of the study members about the specific requirements (trainers/trainees) as well as the obstacles that may face using the electronic training. However, there are statistically significant differences between the average responses of the study members about the specific requirements for the training environment, depending on whether they are trainers or trainees for the benefit of trainees. The study recommends taking care of university’s infrastructure of computers and Internet networks, in order to use electronic training. As well as create electronic training unit within the Deanship of Skills Development and allocation of budget for electronic training. It also recommends that studies be conducted to measure the extent to which to electronic training can be applied in the training facilities of universities and other government agencies.